" Circumcision rulings in Islamic law according to the Shafi’i school - Louay Zaid Saadallah; Shaalan Jassim Mohammed (Islamic Sciences Journal, 2025)
This research examines the rulings on circumcision according to the Shafi'i school of jurisprudence. Shafi'is are considered one of the schools of jurisprudence that adopt balanced views on this matter. In this research, we will review the legal evidence related to circumcision, the points of disagreement among jurists, when it is recommended or obligatory, and the resulting health and social consequences. By analyzing religious texts and scholarly opinions, the research seeks to provide a comprehensive vision that clarifies the status of circumcision in Islamic law and explains the practices followed in various Islamic societies. Some modern views on the subject will also be addressed, contributing to a deeper understanding of the rulings on circumcision in the Shafi'i context. The topic of "Rulings on Circumcision in Islamic Law According to the Shafi'i School" is one of the most important topics, and is considered of great importance. This is achieved by exploring some of the rulings related to circumcision, both for males and females, and presenting them in light of the objectives of Islamic law.